Respiratory syncytial virus - current treatment options and future possibilities for prophylaxis - Hołownia, Weronika; Szewczyk, Kamila; Szewczyk, Bartłomiej; Pytel, Paulina; Krzesłowska, Wiktoria Julia; Wiśniewski, Szymon (Journal of Education, Health and Sport, 2024)
The respiratory syncytial virus (RSV) is responsible for a great deal of lower respiratory tract infections in infants, which result in hospitalizations and death in extreme cases. Almost all children have been infected by the time they turn two years old, but the most vulnerable to developing medical complications are preemies and infants with congenital heart diseases. Understanding the function of RSV F (fusion) protein turned out to be crucial in developing immunoprophylactic drugs, such as Palivizumab and Nirsevimab. Due to limited options of treatment, the search for optimal prophylactic strategy is expanding. This includes monoclonal antibodies and mRNA vaccines. Bringing attention to these methods of treatment will help expand the knowledge of healthcare providers, especially pediatricians and general practitioners.